STUDENTS’ PREFERERNCES TOWARD TEACHERS’ ORAL CORRECTIVE FEEDBACKS ON SPEAKING AT SMK NEGERI 4 MEDAN - Sonya Audry; Nora Ronita Dewi; Puan Suri Mira Annisa (Universitas Negeri Medan, 2020)
The objectives of this study were to investigate the types of teachers’ oral corrective feedback on speaking skill that the students prefer in grade tenth of SMK Negeri 4 Medan. This research used descriptive qualitative method and the data were collected through documentation and interview. The framework undertaken is proposed by Lyster and Ranta and the interview questions were adapted from Thorsteinsen. The data was analyzed in four steps: 1). Data Collection, 2) Data Reduction, 3). Data display, 4). Conclusion and Drawing verification. The findings found that there were 4 kinds of oral corrective feedback that the teachers gave, namely Clarification Request, Elicitation, Explicit Correction, dan Metalinguistic Feedback. The most dominant of teachers’ oral corrective feedback that the students prefer was Explicit Correction. It was 10 data or 41,7%. Based on the analysis interview, the reason why students prefer the type of teachers’ oral corrective feedback on speaking was because it could make the students easy to understand and know the correct anwser not in a long time because the teachers gave it immediately. The finding suggested that the English teacher should give the written feedback to students’ writing task to enable them improve the writing skill.